Gradual and categorical separation in the Phaedo - Peña Raigoza, Jesús Alfonso (2025)
One of the problems for Plato's theory of Ideas is “separation.” And that this has a unique meaning. I propose that Plato saw “separation” non-univocally, believing that it occurs in two important ways. One that I will call “gradual” and another stronger that I will call “categorical”, and that the Phaedo shows these two different types of separation when talking about the soul. This leaves the door open to a moral interpretation of separation and contributes to diluting the mind-body problem. Also, it could support a non-univocal interpretation of the separation of the Forms.